Caspase-1 Inhibitor Reduces Pyroptosis Induced by Brain Death in Kidney - Liu, Weifeng; Yang, Dongjing; Shi, Jihua; Wen, Peihao; Zhang, Jiakai; Wang, Zhihui; Hu, Bowen; Shi, Xiaoyi; Cao, Shengli; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Surgery, 2021)
Brain death (BD) induces an organ-level inflammatory response. However, the underlying mechanisms have not been fully elucidated. Here, we investigated the role of caspase-1-mediated pyroptosis in BD-induced kidney injury in rats. A BD model was established in Sprague-Dawley rats. The rats were intravenously injected with Z-YVAD-FMK 1 h before BD, and sham-operated rats served as controls. After 0, 1, 2, 4, and 6 h of BD, renal function, renal injury, and renal expression of NLRP3, caspase-1, caspase-11, gasdermin D (GSDMD), IL-1β, and IL-18 were assessed using quantitative reverse transcriptase-polymerase chain reaction, western blotting, and immunohistochemistry. Blood urea nitrogen and serum creatinine levels were measured. Additionally, renal tubular epithelial cells (NRK-52E) were subjected to 3 h of hypoxia followed by 6 h of reoxygenation and incubated with Z-YVAD-FMK before hypoxia and reoxygenation. Caspase-11 was knocked-down using small interfering RNA technology. Cell viability and levels of pyroptosis-associated proteins were assessed thereafter. NLRP3, caspase-1, GSDMD, IL-1β, and IL-18 expression levels were upregulated in BD rats. Treatment with Z-YVAD-FMK reduced mRNA and protein levels, improved renal function, and alleviated renal injury. Z-YVAD-FMK effectively reduced pyroptosis in BD rats. Thus, it could be considered as a therapeutic target for BD-induced kidney injury.